2015
DOI: 10.1016/j.heares.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The pupil response reveals increased listening effort when it is difficult to focus attention

Abstract: Recent studies have shown that prior knowledge about where, when, and who is going to talk improves speech intelligibility. How related attentional processes affect cognitive processing load has not been investigated yet. In the current study, three experiments investigated how the pupil dilation response is affected by prior knowledge of target speech location, target speech onset, and who is going to talk. A total of 56 young adults with normal hearing participated. They had to reproduce a target sentence pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 34 publications
2
89
3
1
Order By: Relevance
“…Pupil dilation has long been used as a measure of effort (Beatty, 1982;Bradshaw, 1968;Cabestrero et al, 2009;Granholm and Steinhauer, 2004;Hjortkjaer et al, 2018;Wel and Steenbergen, 2018) and is presently attracting considerable interest in the auditory modality because of evidence that pupil dilation can be used as an objective means with which to evaluate challenges to listening (McGarrigle et al, 2014;Peelle, 2018;Pichora-Fuller et al, 2016). The bulk of existing work has used pupillometry to evaluate listening effort associated with degraded speech (Koelewijn et al, 2012(Koelewijn et al, , 2014(Koelewijn et al, , 2015Kuchinsky et al, 2014;Naylor et al, 2018;Ohlenforst et al, 2017;Wang et al, 2017;Wendt et al, 2016Wendt et al, , 2017Winn et al, 2015Winn et al, , 2018Zekveld et al, 2010Zekveld et al, , 2011Zekveld et al, , 2018. As a result, these tasks inherently challenged both the ability to cope with energetic masking and the ability to sustain attention over time.…”
Section: Introductionmentioning
confidence: 99%
“…Pupil dilation has long been used as a measure of effort (Beatty, 1982;Bradshaw, 1968;Cabestrero et al, 2009;Granholm and Steinhauer, 2004;Hjortkjaer et al, 2018;Wel and Steenbergen, 2018) and is presently attracting considerable interest in the auditory modality because of evidence that pupil dilation can be used as an objective means with which to evaluate challenges to listening (McGarrigle et al, 2014;Peelle, 2018;Pichora-Fuller et al, 2016). The bulk of existing work has used pupillometry to evaluate listening effort associated with degraded speech (Koelewijn et al, 2012(Koelewijn et al, , 2014(Koelewijn et al, , 2015Kuchinsky et al, 2014;Naylor et al, 2018;Ohlenforst et al, 2017;Wang et al, 2017;Wendt et al, 2016Wendt et al, , 2017Winn et al, 2015Winn et al, , 2018Zekveld et al, 2010Zekveld et al, , 2011Zekveld et al, , 2018. As a result, these tasks inherently challenged both the ability to cope with energetic masking and the ability to sustain attention over time.…”
Section: Introductionmentioning
confidence: 99%
“…Its popularity can be 19 attributed to its sensitivity to a wide range of cognitive tasks and processing that relate 20 to the concept of listening effort [3,14,15]. Past studies have shown that pupil size 21 varies with different speech intelligibility, hearing impairment, lexical manipulation, 22 masker type, spectral resolution, memory load and divided/focused attention [4,[16][17][18][19][20][21][22][23]. 23Typically, when task demands increase, for instance, with lower SNR, degraded spectral 24 resolution or more digits to remember, pupil size increases.…”
mentioning
confidence: 99%
“…In combination with the changes in auditory perception, age -related cognitive decline influences processing of auditory information and speech perception (Humes et al, 2012). Focusing on, switching between, and ignoring auditory stimuli increases cognitive load, and adding a hearing impairment increases further load on the cognitive system (Koelewijn et al, 2015). The person struggling to hear the message from a conversation might experience frustration when trying to sift between the different auditory stimuli taxing the cognitive resources (Rudner, Rönnberg & Lunner, 2011).…”
Section: Hearing Hearing Impairment Agementioning
confidence: 99%
“…Listening effort has previously been investigated using various methods (see for example Koelewijn et al, 2015;Larsby et al, 2005;Zekveld et al, 2014)., e.g. pupillometry, which is used to quantify cognitive processing load by measuring pupil dilation in relation to task demands and cognitive load (Koelewijn et al, 2015;Zekveld et al, 2014).…”
Section: Listening Effortmentioning
confidence: 99%
See 1 more Smart Citation